The Roman philosophers : from the time of Cato the Censor to the death of Marcus Aurelius - Morford, Mark P. O., 1929-2019 (Routledge/Taylor & Francis, 2002)
Mark Morford provides a lively, succinct and comprehensive survey of the philosophers of the Roman world, from Cato the Censor in 155 BCE to the death of Marcus Aurelius in 180 CE.